ANALISIS KINERJA KEPALA SEKOLAH DALAM PENGELOLAAN DANA BOS DI SMPN SATAP 6 KABUPATEN TANJUNG JABUNG TIMUR - Mohamad Muspawi; Zainul Havis; M Nurmawan; K.A. Rahman (Jurnal Tunas Pendidikan, 2026)
The principal's performance analysis is the ability of the school as a BOS fund management institution in optimizing the existing financial functions to achieve the purpose of using these resources. The principal has not fully adjusted the availability of funds to the needs of the school and the financial planning carried out by the principal is still not in accordance with the real needs of the school. Although this condition was not fully expected by the principal and a number of teachers, because so far the need for BOS funds has not been supported by school committee funds because school committee fees have been abolished. This research uses a qualitative model with a case study approach. Data collection techniques were carried out through interviews, and document studies. Data analysis techniques in the form of data reduction, data presentation, and conclusions. The subjects in this study were the BOS fund team, the principal, treasurer, committee, 1 teacher and student guardian were the samples of this study. The conclusion is: Analysis of the Principal's Work in Management of BOS Funds at SMPN SATAP 6 Tanjung Jabung Timur Regency is carried out based on the authority given by the principal so that BOS Management can be channeled in accordance with the objectives to be achieved. As for what the Principal does, by means of; first develop a plan based on the priority scale of school needs. Second Determine the work program and details of the school program. Third, calculate the rational budget for each work program. Fourth, allocate BOS funds for each activity program based on the BOS technical guidelines. Fifth, Management of BOS Funds is in accordance with the objectives of the existing BOS Funds in the technical guidelines. Sixth, carry out supervision in the management of BOS funds.